2009
DOI: 10.2337/db09-0551
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Storage and Glucose Homeostasis in Mice Null for the Granule Zinc Transporter ZnT8 and Studies of the Type 2 Diabetes–Associated Variants

Abstract: OBJECTIVEZinc ions are essential for the formation of hexameric insulin and hormone crystallization. A nonsynonymous single nucleotide polymorphism rs13266634 in the SLC30A8 gene, encoding the secretory granule zinc transporter ZnT8, is associated with type 2 diabetes. We describe the effects of deleting the ZnT8 gene in mice and explore the action of the at-risk allele.RESEARCH DESIGN AND METHODSSlc30a8 null mice were generated and backcrossed at least twice onto a C57BL/6J background. Glucose and insulin tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
443
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 354 publications
(496 citation statements)
references
References 51 publications
41
443
3
1
Order By: Relevance
“…More efficient accumulation of zinc in secretory granules in cells expressing ZnT-8 W325, as demonstrated by previous studies, 13,25 appears to account for this effect. Importantly, the different effects of the two variants on insulin secretion became more pronounced when b-cell insulin secretion was suppressed by CsA.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…More efficient accumulation of zinc in secretory granules in cells expressing ZnT-8 W325, as demonstrated by previous studies, 13,25 appears to account for this effect. Importantly, the different effects of the two variants on insulin secretion became more pronounced when b-cell insulin secretion was suppressed by CsA.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, measurement of mRNA expression using real-time PCR showed that neither CsA nor high glucose had a measurable effect on insulin mRNA expression, at least in the experimental time frame used for GSIS study (Figure 3b). As the zinc transport activity of ZnT-8 has been positively correlated with insulin-secreting capacity, 11,14,25 we performed a vesicle transport assay to determine whether the polymorphism confers differential zinc transport activity. Vesicles expressing ZnT-8 W325 showed increased transport of 65 Zn into vesicles when compared with those expressing ZnT-8 R325 (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A crystal structure of mammalian ZnT8 is not yet available; consequently, the data on protein structure-function relationships and effect of the SNPs on them are based on the bacterial homolog YiiP, which has 51.8% sequence homology with the mammalian protein [74,75]. Arginine/Tryptophan-325 is located in an area involved in transporter homodimerization but as the side chains point away from the dimerization interface, it is unlikely that the R325W substitution prevents dimerization or Zn 2+ binding (Figure 2) [76,77].However, it is conceivable that the positive charge of the R-side chain may hamper molecular interactions, for instance with unidentified Zn 2+ -binding proteins which might interact with ZnT8 to facilitate zinc transport. Supporting this view, we found by overexpressing either isoform in a β cell line and measuring zinc in vesicles with Zinquin that in presence of supraphysiological zinc concentration, zinc accumulation into granules was significantly higher for W-versus R-form.…”
mentioning
confidence: 99%